Analysis of the Implementation of the Islamic Boarding School Curriculum in Enhancing Students' Competence in the Tahfidzul Qur'an Program - Nugraha, Muhamad Arif; Kusuma, Deni Tata; Pamungkas, Muhamad Imam (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study analyzes the implementation of the Islamic boarding school curriculum in enhancing students' competencies in the Tahfidzul Qur'an program at Pesantren Darul Ulum Gunung Halu, Bandung. Key challenges include unsystematic evaluation, varied teaching methods, and differing levels of student discipline. Using a qualitative case study approach, this research collects data through observations and interviews with administrators and students. Findings show that the tahfidz curriculum is implemented through muroja’ah, tasmi’, and tadarus methods, with evaluations consisting of daily recitations, semester exams, and annual assessments. The program’s success is driven by effective management, strict discipline, and competency-based learning. Systematic curriculum planning and periodic evaluations significantly enhance the quality of tahfidz education. Through structured learning, discipline, and a supportive environment, the pesantren successfully produces students who not only excel in Qur'anic memorization but also internalize and practice Islamic values in daily life.